(3UhQ GdchGcHs - (3YHO GdQMef Hf YeQ Hf Sgd GdUhaj GdQGRqj, CHh GdMSjf,J (B376 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdhGMO GdYOd bGd Efi QCjJ cKjQkG ef GdfGS jNhVhf ai WdH eYQaI GdchGcH GdKGHJI hehGbYgG ai Gdadc s
(3BNQgG (B:s
(3hef GdNGeS GdPi Ydi GdHWf Edi GdeZQH hGdLfhH bQH ef KdKI CPQY hgPg UhQJG GdMhJ GdLfhHi Ydi eG jQi ai GdSeGA hYdi eG jQi ai GdcQI s
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B319 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B5 - (3U (B162s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1084s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3Gdadcs